Fabrication and assessment of reduced graphene oxide and silver nanocomposites using Clinacanthus nutans (Burm.f.) Lindau for biomedical applications - Parmal @ Perumal, Dharshini (2023)
Graphene derivatives have garnered substantial interest due to their remarkable properties. The incorporation of graphene derivatives with metal nanoparticles forms nanocomposite that enhances their properties and potential applications in the field of medicine. Silver nanoparticles (AgNPs) are extensively utilised due to their excellent physical and biological properties. During the synthesis process, uncontrolled growth of silver ion can lead to agglomeration. This makes them to lose their desirable properties. Graphene derivative serves as a good support to stabilize AgNPs. The fabrication of nanocomposite employs a green synthesis compared to conventional physical and chemical methods. The green synthesis utilising natural and renewable resources is cost-effective, environmentally friendly, and non-toxic. In the present study, one pot synthesis of reduced graphene oxide decorated silver (rGO-Ag) nanocomposite was successfully prepared utilizing the extract of medicinal plant, Clinacanthus nutans. The extract makes it a potent reducing agent for the reduction of graphene oxide (GO) and silver nitrate solution as a precursor to produce nanocomposite. The synthesis of rGO-Ag nanocomposite was conducted using the selected conditions: 100 °C (temperature), 50 % (leaf extract concentration), and 6h (time). The properties of rGO-Ag nanocomposite were characterized by ultraviolet-visible spectroscopy (UV-Vis), x-ray diffraction spectroscopy (XRD), Fourier transform infrared spectroscopy (FTIR), raman spectroscopy, field emission scanning electron microscopy (FESEM), and energy dispersive X-ray spectroscopy (EDS). The absorbance peak observed at 425 nm and 263 nm indicates the formation of rGO-Ag nanocomposite. The XRD and FTIR pattern showed that the rGO-Ag nanocomposite matched the pattern of AgNPs. The raman analysis showed a D to G peak intensity ratio of 0.56. FESEM image revealed the spherical shaped AgNPs of average size 48 ± 11 nm deposited on the surface of rGO. The EDS analysis revealed the weight ratio of Ag (84.3 %) and C (9.1 %). The antibacterial activity of the as-synthesized sample against Escherichia coli (E.coli) and Staphylococcus aureus (S. aureus) bacterial strain were studied. GO, leaf extract, and rGO did not show inhibitory activity whereas AgNPs demonstrated the best antibacterial activity against E. coli compared to S. aureus. The rGO-Ag nanocomposite showed excellent antibacterial activity against both E. coli (11.86 ± 0.29 mm) and S. aureus (11.99 ± 0.26 mm) strains. The as-synthesized sample was also assessed for their potential as anticancer agent against human lung cancer cell (A549) and human epithelial colorectal cancer cell (Caco2) using XTT assay. GO and rGO showed low cytotoxicity against A549 cells while no cytotoxicity against Caco2 cells. AgNPs displayed dose-dependent cytotoxicity against both cells. At the highest concentration of 25 μg/mL, the cell viability of rGO-Ag nanocomposite towards A549 cells was 80 % (IC50 value 3.509 μg/mL) and Caco2 cells was 79 % (IC50 value 2.578 μg/mL), respectively. The ecotoxicity studies revealed that at low concentration (0.001 mg/mL) rGO-Ag nanocomposite exhibit more than 50 % hatching rate of Artemia salina cysts. In summary, this work provides the promising green synthesis by utilizing non-toxic and environmentally friendly reducing agent to produce rGO-Ag nanocomposite for biomedical applications.